Implikasi pada Pernyataan Sehari-hari - Sudiarto Sudiarto (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2022)
This study aims to facilitate the understanding of if-then statements or implications in everyday statements based on mathematical logic. The research method used is applied literature study and concept analysis. The researcher analyzes the implications of everyday statements based on the relationship between cause and effect statements using set theory which is described by a Venn Diagram. The pattern of compound statement relationships in the Venn Diagram is used to determine the truth value of the implications. There are seven patterns of causal statement relationships in everyday statements depicted in the Venn Diagram. Based on the pattern of the relationship, there are seven types of implications in everyday statements, namely: (1) Section Implications which in mathematical logic are called Implications, (2) Scope Implications, (3) Intersecting Implications, (4) Equivalence Implications, which in Mathematics called Biimplications, (5) Independence Implication, (6) Different Universal Implication, and (7) Negation Implication. The results of this study indicate that giving examples of mathematical logic statements using everyday statements must consider the pattern of causal statements to make it easier to determine the truth value.